Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

5-(-3)=2
6-(-2)=4
How can you remove negative counters form a set of positive counters? What is net effect?


Sagot :

Because if there are two - to meet the plus

Answer with explanation:

⇒The two expressions

 5-(-3)=2

6-(-2)=4

 is Incorrect.

1.→ 5 - (-3)

- (-3)=Additive inverse of -3, will be equal to 3.

So, it will be equal to =5+3

          =8

2.→ 6 - (-2)

- (-2)=Additive inverse of -2, will be equal to 2.

So, it will be equal to =6+2

          =8